Increased nuclear expression of DNA damage inducible transcript 4 can serve as a potential prognostic biomarker in patients with gliomas: a study based on data mining and experimental tools - Alireza Sadeghipour; Fahimeh Fattahi; Zahra Madjd; Fatemeh Tajik; Farnoosh Sedaghati; Leili Saeednejad Zanjani (Discover Oncology)
Abstract Introduction DNA damage-inducible transcript 4 (DDIT4), induced under cellular stress conditions, has been implicated in malignancies due to its abnormal expression patterns. Materials and methods The expression of DDIT4 at the mRNA level and its potential role as a prognostic biomarker in gliomas were analyzed using the GEPIA tool. To validate these findings, DDIT4 protein expression levels and their prognostic significance were examined in tissue microarrays from glioma patients using immunohistochemistry in clinical samples. Results Bioinformatics analysis revealed that DDIT4 overexpression in glioma tumors and its high mRNA expression levels are associated with poor outcomes, likely through mTOR signaling. At the protein level, positive nuclear DDIT4 expression was linked to higher histological grades and temozolomide treatment. Kaplan–Meier survival analysis demonstrated that positive nuclear DDIT4 expression is a significant predictor of poor disease-specific survival (DSS) and recurrence-free survival (RFS). Additionally, nuclear DDIT4 expression was identified as an independent prognostic factor for DSS. Conclusion Our findings suggest that nuclear DDIT4 expression may serve as a potential prognostic biomarker and therapeutic target in glioma patients. However, further studies with larger sample sizes and long-term follow-ups are needed to validate these observations and confirm their clinical relevance.